Das Wittgenstein’sche Sprachspiel als Mittel praxisdienlicher und didaktikbezogener Reflexion (mathematica didactica, 2018)
The Wittgenstein language game is used frequently in theoretical mathematical didactic articles as an instrument for the interpretation of meaning-forming processes. In this article, the practicality of the Wittgenstein language game as a means of profitable didactic-relevant reflection in various contexts is demonstrated by means of practical examples. The results of such reflections can be used as a basis for the didactic preparation of mathematical content.